The Present and Future of Virology in the Czech Republic—A New Phoenix Made of Ashes? - Tomas Ruml (Viruses, 2022)
The Czech Republic, a part of the former Czechoslovakia, has been at the forefront of several research directions in virology, genetics and physiology [...]